Marching on a path less travelled : Finding a breakthrough beyond breakdowns - Vir, Raju (Indian Journal of Training and Development)
The pandemic has brought C-suite executives at crossroads to choose the right path for steering the organization. Which path is better: to gear up and enhance business capabilities and operational excellence through thoughtful initiatives such as cost optimization, building critical skills of employees, orto make hasty reactions including lay-offs, downsizing and diminution of employees. It is a challenge to C-suite executives to think from inside out and choose the right path and accomplish a breakthrough beyond breakdown. This study shows how these executives viewed pandemic as an unprecedented opportunity to capitalize their personal leadership skills (solid initiatives), nurtured critical (lateral) thinking skills, pruned emotional resilience and sharpened their problem-solving (crisis management) skills, in order to develop new leadership skills. A constructivist approach and thirty (30) C-Suite executives were chosen for this qualitative study, with a view to understand the extent to which executives adopted a path less travelled to reach a Breakthrough. It was found that these executives constructed knowledge beyond the obvious, through their own interpretations of challenges. Findings reveal that these executives accomplished this task by choosing a path less traveled, the path of empathy and compassion, the path of agility and resilience, and the path of convergence to rebuild a shared business vision. Reproduced
Keywords: Constructivism, Decision making, Emotional resilience, New learning, Crisis management